Europa Oxalá. - Rebelo Correia, Ana (S.l. : Edições Afrontamento, 2021)
Mpane, Aimé ; Ntakiyica, Aimé ; Bunga, Carlos ; Jasse, Délio ; Kokene-Dorléans, Djamel ; Baghriche, Fayçal ; Vidal, Francisco ; Cobra, John K. ; Ntjam, Josèfa ; Kameli, Katia ; Andrialavidrazana, Malala ; Carvalho, Márcio ; Bourouissa, Mohamed ; de Miranda, Mónica ; Barreto, Nú ; Valente Pimentel, Pauliana ; Paixão, Pedro A.H. ; Belouaar, Sabrina ; Baloji, Sammy ; Mujinga, Sandra ; Sadik, Sara
Europa Oxalá, Koninklijk Museum voor Midden-Afrika - AfricaMuseum, Tervuren, 6 oktober 2022 tot 5 maart 2023
boek